Only time will tell - Archer, Jeffrey 1940- (Archer, Jeffrey 1940- Clifton chronicles, 2011)
From the popular author of Kane and Abel and A Prisoner of Birth comes the story of one family across generations, across oceans, from heartbreak to triumph. The epic tale of Harry Clifton's life begins in 1920, with the words, "I was told that my father was killed in the war." A dock worker in Bristol, Harry never knew his father, but he learns about life on the docks from his uncle who expects Harry to join him at the shipyard once he's left school. But then his unexpected gift wins him a scholarship to an exclusive boys' school, and his life will never be the same again. As he enters into adulthood, Harry finally learns how his father really died, but the awful truth only leads him to question who was his father? Is he the son of Arthur Clifton, a stevedore who spent his whole life on the docks, or the first-born son of a scion of West Country society, whose family owns a shipping line? This introductory novel in The Clifton Chronicles includes a cast of colorful characters and takes us from the ravages of the Great War to the outbreak of the Second World War, when Harry must decide whether to take up a place at Oxford or join the navy and go to war with Hitler's Germany. From the docks of working-class England to the bustling streets of 1940 New York City, Only Time Will Tell takes readers on a journey through to future volumes, which will bring to life one hundred years of recent history to reveal a family story that neither the reader nor Harry Clifton himself could ever have imagined.